Contact dermatitis among marking nut workers in rural India - U Kawalkar; R Sangale; A Gaidhane; A Mankar; P Kogade; S Aggarwal (Occupational Medicine, 2026)
Abstract Background Informal processing of Semecarpus anacardium (marking nut) provides livelihood to many women in rural India. The nut contains potent phenolic compounds with strong irritant and allergenic properties, yet occupational contact dermatitis related to this exposure remains poorly documented in community settings. Aims To describe the prevalence, clinical severity and occupational determinants of contact dermatitis among female informal workers involved in marking nut processing in rural Vidarbha, India. Methods A community-based cross-sectional study was conducted among all eligible female workers engaged in marking nut processing in a rural village in Maharashtra. Trained healthcare workers performed clinical skin examinations. Contact dermatitis was diagnosed based on clinical features and occupational exposure history, and severity was graded as mild, moderate or severe. Associations between dermatitis severity and selected sociodemographic and occupational factors were analysed. Results A total of 125 women were included. Recurrent work-related contact dermatitis was reported by 115 participants (92%), although only 5 (4%) had clinically active disease at the time of examination. On clinical assessment, 95 (76%) participants had moderate to severe dermatitis. Greater disease severity was significantly associated with increasing age, longer occupational exposure, longer daily working hours, lower educational status and engagement in higher-risk activities such as roasting and oil extraction. Conclusions Contact dermatitis due to S. anacardium is a significant but neglected occupational health problem among women in informal rural labour. Awareness, health education and safer handling practices are urgently needed to reduce disease burden.